An endoribonuclease-based feedforward controller for decoupling resource-limited genetic modules in mammalian cells - Ross D. Jones (Nature Portfolio, 2020)
Accurately predicting the behaviour of a genetic circuit remains difficult due to the lack of modularity. Here the authors quantify the effects of resource loading in mammalian systems and develop an endoribonuclease-based feedfoward controller to adapt gene expression to the effects of resource loading.